CLINICOPATHOLOGICAL CHARACTERISTICS AND OUTCOMES OF VIDEO ENDOSCOPIC INGUINAL LYMPHADENECTOMY FOR PENILE CANCER: EXPERIENCE FROM BINH DAN HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinicopathological characteristics and evaluate surgical outcomes of video endoscopic inguinal lymphadenectomy (VEIL) for penile cancer at Binh Dan Hospital.Methods: A prospective descriptive case series was conducted from May 2023 to June 2025 at Binh Dan Hospital. A total of 38 penile cancer patients underwent bilateral VEIL. Variables included clinicopathological features, surgical outcomes, complications (Clavien-Dindo classification), and oncological results.Results: Mean age of the patients was 54.6 ± 10.9 (32-73 years). pT3 accounted for 60.5% and cN2 for 71.1%; G1 histological grade predominated (60.5%). All 38 cases (100%) completed bilateral VEIL without conversion. Mean total operative time was 189.5 ± 23.2 min (120-240 min). The great saphenous vein was preserved in 97.4% per side. Mean lymph node yield was 16.0 ± 2.3 per patient (range 13-23). Pathological staging: pN0 78.9%; pN1 13.2%; pN2 7.9%; extranodal extension detected in 1 case (2.6%). Subclinical lymphocele 68.4%; symptomatic lymphocele 21.1%. Wound infection 5.3%; no skin necrosis or deep vein thrombosis. Mean hospital stay 5.6 ± 2.3 days. Recurrence rate 13.2%; mean disease-free survival 26.2 ± 13.0 months.Conclusion: VEIL is a feasible, safe and oncologically adequate inguinal lymphadenectomy technique for penile cancer, with low major complication rates and adequate node yield per EAU-ASCO (2026) criteria.
Keywords: VEIL, penile cancer, video endoscopic inguinal lymphadenectomy, complications, oncological outcomes.